TELEROENTGENOMETRIC PARAMETERS OF THE HYOID BONE AND TONGUE IN UKRAINIAN BOYS AND GIRLS WITH AN ORTHOGNATHIC BITE WITHOUT AND TAKING INTO ACCOUNT THE TYPE OF FACE - Kostiuchenko-Faifor, O.S.; Gunas, I.V.; Veretelnyk, S.P.; Popova, O.I.; Dudik, O.P. (World of Medicine and Biology, 2022)
In the course of the study, pronounced manifestations of sexual dimorphism (higher values in young men) of teleroentgenometric parameters of the hyoid bone and tongue were established in the Ukrainian population of youth without pathology of the upper respiratory tract with an orthognathic bite, both in representatives without taking into account the type of face and, in most cases, in young men with different types of faces. Also, between young women and young men with different face types, reliable or trends of differences in the values of these parameters were established – young women with a narrow face have smaller values of the VT distance and the TA area than young women with very wide and wide face types; and young men with a narrow face have larger values of the AH-FH, AH-MP and H-VT distances than representatives with very wide and wide face types.
Keywords: teleroentgenography; cephalometry; hyoid bone; tongue; young men; young women; orthognathic bite; facial types